Studies in the Masoretic Tradition of the Hebrew Bible - Crowther, Daniel J.; Hornkohl, Aaron D.; Khan, Geoffrey (Semitic Languages and Cultures, 2022)
This volume brings together papers on topics relating to the transmission of the Hebrew Bible from Late Antiquity to the Early Modern period. We refer to this broadly in the title of the volume as the 'Masoretic Tradition'. The papers are innovative studies of a range of aspects of this Masoretic tradition at various periods, many of them presenting hitherto unstudied primary sources. They focus on traditions of vocalisation signs and accent signs, traditions of oral reading, traditions of Masoretic notes, as well as Rabbinic and exegetical texts. The contributors include established scholars of the field and early-career researchers.